The Effects of The Changing Locus on Lasi’s Hibridity in The Red Bekisar by Ahmad Tohari - Asmarani, Ratna (Faculty of Humanities, Diponegoro University, 2023)
This paper deals with Ahmad Tohari’s English-translated novel entitled The Red Bekisar. The focus is on the effects of the changing locus on the female protagonist’s hybridity. To support the analysis, several concepts are used, namely, the concepts of hybridity, mimicry, and cultural identity in postcolonial literature. Using feminist literary criticism as the frame of analysis, the general research method used is qualitative research, supported by library research. For the literary analysis, the contextual research method is applied, in which, by considering the character, conflict, and setting, the focus is on the female protagonist’s hybridity and how her hybridity is regarded by people from different loci. The results show that the female character, Lasi, has a different life because of her Javanese-Japanese mixed blood. In the remote village of Karangsoga, her hybridity is scorned, but in the big city of Jakarta, her hybridity is highly appreciated. However, she is treated like an object, a valuable doll that can be transferred to different owners. Her resistance indicates that her agency as a human being emerges when she is cornered.